Penerapan Model Kooperatif Tipe Group Investigation terhadap Hasil Belajar Pendidikan Pancasila Siswa Kelas IV - Viranita, Dinda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to determine the completeness of the learning outcomes of Pancasila education of grade IV students at SD Negeri 53 Lubuklinggau after being given a cooperative model of group investigation type. This research method uses a pre-experimental design research method with a Pre-test and Post-test experimental design. The instrument used by the researcher was in the form of multiple-choice choices totaling 16 questions. The results of the post-test evaluation showed that most students obtained adequate scores, indicating a significant increase in their understanding of the Pancasila material. The implications of this study guide students to participate actively in collaborative learning, teachers to develop teaching strategies that involve active student interaction, students to further explore collaborative learning methods, and schools to consider integrating cooperative models into the character education curriculum. Keywords: Cooperative, Group Investigation, Pancasila, Learning Outcomes